Timely tumor response analysis after preoperative chemoradiotherapy and curative surgery in locally advanced rectal cancer: A multi-institutional study for optimal surgical timing in rectal cancer. Issue 3 (June 2016) - Kwak, Yoo-Kang; Kim, Kyubo; Lee, Jong Hoon; Kim, Sung Hwan; Cho, Hyeon Min; Kim, Dae Yong; Kim, Tae Hyun; Kim, Sun Young; Baek, Ji Yeon; Oh, Jae Hwan; Nam, Taek Keun; Yoon, Mee Sun; et al.
Abstract: Background and purpose: The definite surgical timing in rectal cancer after preoperative chemoradiotherapy (CRT) has not yet been fully examined. We assess the tumor response and identify the optimal operation timing after preoperative CRT in rectal cancer. Methods and materials: The study included data of 1786 patients with locally advanced rectal cancer (cT3-4N0-2M0). They received preoperative CRT followed by total mesorectal excision. Total radiation dose was 50.4 Gy in 28 fractions. Interval time between preoperative CRT and surgery ranged from 2 to 26 weeks, with a median interval of 7.2 weeks. Primary endpoint was to evaluate the period of highest downstaging and pathological complete response (ypCR) rates to determine the optimal timing for curative surgery after CRT. Results: Downstaging rates peaked between 6 and 7 weeks after CRT and declined afterward. ypCR rates increased from 5 to 6 weeks after CRT and decreased after 9 to 10 weeks. Downstaging rates were similar between the two arms showing 36.9% in the early arm (⩽7 weeks) and 37.0% in the delayed arm (>7 weeks). ypCR rates were significantly higher in the delayed arm, as compared to the early arm (12.3% vs. 8.6%, p = 0.011). The delayed arm had higher sphincter preservation rates than the early arm with a marginal significance (92.4% vs. 89.9%, p = 0.078). There was no statistically significant difference regarding relapse-free survival and overall survival between the two arms. Conclusions: ypCR rates increased after 5 weeks and decreased after 10 weeks and the delayed (>7 weeks after CRT) group showed significantly increased ypCR rates than the early arm (⩽7 weeks after CR). The optimal timing for curative surgery in rectal cancer when tumor response is maximal is after 7 weeks and before 10 weeks following preoperative CRT.